Determination of the relative contribution of phenolic antioxidants in orange juice by voltammetric methods - Sousa, W. R.; da Rocha, C.; Cardoso, C. L.; Silva, DHS; Zanoni, Maria Valnice Boldrin [UNESP] (Elsevier B.V., 2004)
The electrochemical oxidation of caffeic, chlorogenic, sinapic, ferulic and p-coumaric acids was investigated by cyclic voltammetry on acetate buffer pH 5.6 on glassy carbon electrode and modified glassy carbon electrode. According to their voltammetric behavior, the antioxidant activity of these phenolic acids was evaluated and the results pointed to the following sequence: caffeic acid (E-a = +0.31 V) > chlorogenic acid (+ 0.38 V) > sinapic acid (+ 0.45 V) > ferulic acid (+ 0.53 V) >p-coumaric acid (+ 0.73 V). The results were confirmed by DPPH test, which evidenced the strongest antiradical activity for compounds possessing the cathecol moiety (caffeic and chlorogenic acids). Linear calibration graphs were obtained for their determination at concentrations from 1 x 10(-4) to 1 x 10(-3) mol L-1. The method was applied to orange juice. Selectivity was illustrated by the analysis of caffeic and chlorogenic acids electrodeposited on a glassy carbon electrode previously modified by electrochemical activation in the presence of ascorbic acid. (C) 2003 Elsevier B.V. All rights reserved.
Keywords: phenolic antioxidants; voltammetric methods; electrochemical oxidation; orange juice